From Loanwords to Lexical Innovation: COVID-19 Buzzwords in Japanese Discourse - Takako Kawabata (TRANSBAHASA, 2025)
The COVID-19 pandemic has significantly influenced language, leading to the emergence of numerous neologisms worldwide to describe unprecedented changes in lifestyle. In Japan, English-based loanwords were frequently adopted alongside Japanese terms in pandemic discourse, despite the availability of Japanese equivalents. This study explores COVID-19-related buzzwords in Japan, focusing on their formation and usage. It addresses three key research questions: 1) What types of COVID-19-related neologisms emerged in Japanese? 2) What are the distinguishing features of these neologisms? and 3) What roles do English loanwords play? Using linguistic and sociolinguistic approaches, the study examines terms nominated for two prominent new word and buzzword awards in Japan. The findings reveal four categories of neologisms: Japanese words, English loanwords, concomitants of Japanese and English loanwords, and hybrids of Japanese and English words. Furthermore, the study identifies four primary processes: nominalisation, word formation, lexical deviation, and borrowing. The analysis highlights the sociolinguistic impact of these neologisms, demonstrating how they reflect Japan's cultural and generational dynamics, facilitate engagement with global public health discourse, and underscore tensions around accessibility for older demographics. This research contributes to understanding language evolution in response to international events and offers a novel perspective on the impact of the COVID-19 pandemic on the Japanese language.